(untitled) (Journal of the College of Education for Women, 2019)
Abstract:This research deals with two topice of the modern stylistic topics among.It attempts to give answers on them .the contemporary Arab scholarsThe first topic: The application of modern western stylistics on theQuraanic text.The second topic: The roots of stylistics in the Arabic rhetoric history.